Specific Effects of a recB Mutation on the HfrH Strain of Escherichia coli - Đermić, Damir (American Society for Microbiology, 1999)
The recB268::Tn10 mutation was introduced into the HfrH strain of Escherichia coli. Compared with recB F(−) and recB F(+) cells, the viability of this mutant strain was much lower. Compared with wild-type HfrH, the recB derivative donated much shorter fragments of its chromosome to the recipient. It is suggested that the recB gene product (i.e., RecBCD enzyme) participates in Hfr transfer.